Deterministic entanglement swapping with an ion-trap quantum computer - Riebe, M.; Monz, T.; Kim, K.; Villar, A. S.; Schindler, P.; Chwalla, M.; Hennrich, M.; Blatt, R. (Nature physics, 2008)
Entanglement swapping—a protocol for entangling remote quantum systems without the requirement of direct interaction between them—has been implemented in a completely deterministic fashion, allowing to prepare well-defined entangled states on demand. Entanglement—once only a subject of disputes about the foundation of quantum mechanics—has today become an essential issue in the emerging field of quantum information processing, promising a number of applications, including secure communication, teleportation and powerful quantum computation. Therefore, a focus of current experimental work in the field of quantum information is the creation and manipulation of entangled quantum systems. Here, we present our results on entangling two qubits in an ion-trap quantum processor not through a direct interaction of the ion qubits but instead through the action of a protocol known as entanglement swapping 1 . Our ion-trap system enables us to implement all steps of the entanglement swapping protocol in a fully deterministic way. Thus, two ion qubits can be prepared on demand in a well-defined entangled state. This particular feature may facilitate the implementation of quantum repeaters 2 or aid in distributing entangled states in ion-trap quantum computers 3 .